Remarks on charged vortices in the Maxwell-Chern-Simons model - Colatto, L. P.; Helayel, J. A.; Hott, M.; Moura-Melo, W. A. (Elsevier B.V., 2003)
We study vortex-like configuration in Maxwell-Chern-Simons electrodynamics. Attention is paid to the similarity it shares with the Nielsen-Olesen solutions at large distances. A magnetic symmetry between a point-like and an azimuthal-like current in this framework is also pointed out. Furthermore, we address the issue of a neutral spinless particle interacting with a charged vortex, and obtain that the Aharonov-Casher-type phase depends upon mass and distance parameters. (C) 2003 Published by Elsevier B.V.